Zmiany na rynku jabłek w krajach Unii Europejskiej w latach 2000–2010 - Borowska, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
The article presents information concerning changes undergoing on the EU market of fresh apples between 2000–2010. The author shows changes in production, consumption, foreign trade and prices, of the main stakeholders (producers, consumers, exporters and importers), including Poland. Secondary sources of information were used for the analysis, originating from Faostat 2012 and GUS data bases. The analysis was carried out under a research project (grant agreement No 3745/B/H03/2011/40), which was funded by National Science Centre. The analysis involved comparative as well as descriptive methods.